A life for autoimmune blistering diseases: in memoriam Detlef Zillikens - Hundt, Jennifer E.; Sadik, Christian D.; van Beek, Nina; Busch, Hauke; Caux, Frédéric; Goebeler, Matthias; Hammers, Christoph M.; Hartmann, Karin; Hashimoto, Takashi; Ibrahim, Saleh; Kasperkiewicz, Michael; Murrell, Dedee F.; et al. (Frontiers in Immunology, 2023)
aged only 64. He dedicated his professional life to autoimmune blistering diseases (AIBD) and built his department into one of the world's leading centers for these diseases. Herein, his professional life and the impact on the field of AIBD and the research landscape at the University of Lübeck are addressed. With his warm, integrative, open-minded, ever optimistic attitude he was a highly reliable colleague, mentor, and friend to many in the field including each of the authors. Combined with his in-depth knowledge of dermatology, interest in many fields of life science, and hard work, Detlef Zillikens initiated the founding of two independent research institutes, the Lübeck Institute of Experimental Dermatology and the Institute and Comprehensive Center for Inflammation Medicine. He was also instrumental to establish the Center for Research of Inflamed Skin, where in a new research building over 140 scientists pursue research questions related to skin inflammation. By inviting numerous researchers and clinicians to his department and hosting two large international meetings he brought the field of AIBD much closer together and inspired multiple national and international research initiatives. His ideas will live on and grow in many of his colleagues and mentees.